Intervention of mitochondrial dysfunction-oxidative stress-dependent apoptosis as a possible neuroprotective mechanism of α-lipoic acid against rotenone-induced parkinsonism and l-dopa toxicity - Abdin, Amany A.; Sarhan, Naglaa I. (Neuroscience research, 2011)
► Mitochondria dysfunction-oxidative stress-apoptosis have a role in PD pathogenesis. ► α-Lipoic acid provided early neuroprotection by intervention of this pathogenesis. ► l-Dopa was found to deteriorate PD pathogenesis despite symptomatic motor relief. ► α-Lipoic acid efficiently halted the deleterious effects of l-dopa. ► α-Lipoic acid recommended as a disease-modifying therapy with l-dopa in early PD. The current study evidenced hypothesis that mitochondrial dysfunction-oxidative stress-dependent apoptotic pathways play a critical role in degeneration of dopaminergic neurons in Parkinson's disease. Model of rotenone-induced parkinsonism in rats produced decrease in striatal complex I activity and reduced glutathione with increase in nitrites concentration and caspase-3 activity. This was confirmed by significant correlation of catalepsy score with neurochemical parameters. Moreover, electron microscopic examination of striatal neurons displayed ultrastructure affection as hyperchromatic nuclei and disrupted mitochondria that are typical features of undergoing apoptosis. Administration of l-dopa as replacement therapy, although caused symptomatic improvement in catalepsy score, but further worsening in neurochemical parameters. Therefore, efforts are not only to improve effect of l-dopa, but also to introduce drugs provide antiparkinsonian and neuroprotective effects. In this study, α-lipoic acid exhibited noticeable neuroprotective effects by a mechanism via intervention of mitochondrial dysfunction-oxidative stress-dependent apoptotic pathways. Combination of α-lipoic acid efficiently halting deleterious toxic effects of l-dopa, revealed normalization of catalepsy score in addition to amelioration of neurochemical parameters and apparent preservation of striatal ultrastructure integrity, indicating benefit of both symptomatic and neuroprotective therapy. In conclusion, α-lipoic acid could be recommended as a disease-modifying therapy when given with l-dopa early in course of Parkinson's disease.